Pengaruh Kompensasi terhadap Implementasi Entrepreneurial Government dan Kinerja Aparatur Pemerintah Daerah (Studi pada Pemerintah Daerah Provinsi Gorontalo) - Niode, Idris Yanto (Jurnal Aplikasi Manajemen, 2012)
Research aims to examine and confirm in manner of empiric (1) whether the compensation has direct and positive effect on the implementation of entrepreneurial government; (2) whether the applicationof compensation system directly and positively influences the performances of local government officers; (3) whether the implementation of entrepreneurial government effects directs and positives manners onthe performance of local government officers; (4) whether the compensation gives effect indirectly and positively on the performance of government officers through the implementation of entrepreneurial governmentas intervening variables Results of research indicate that: (1) the compensation provision system consisting of local performance benefit (TKD), promotion, self development, admission, and facility, provideseffect directly and positively to the implementation of entrepreneurial government; (2) the compensation provision system consisting of local performance benefit (TKD), promotion, self development, admission,and facility, gives effect directly and positively to the performance of local government officers; (3) the implementation of entrepreneurial government applied and prevailed into the organization life of the localgovernment of Gorontalo Province has direct and positive effect on the performance of local government officers; (4) the provision of compensation extends positively indirect effec on the improvement of theperformance of local government officers through the implementation of entrepreneurial government.